2019
DOI: 10.4314/bajopas.v11i1.24s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and interpretation of high resolution aeromagnetic data over Kabo town and its adjoining areas, in Northwestern Nigeria

Abstract: INTRODUCTION Geophysics is a subject of natural science is concerned with the physical processes and physical properties of the Earth and its surrounding space environment using the physics principles to the study of the earth's interior. It is therefore a threeof the principles of Physics to the Earth, Moon and Planets (Reynolds, Geophysics is applied to societal needs, such as mineral resources, mitigation of natural hazards and environmental protection. Geophysical survey data are used to analyze potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The lineament density map and the rose diagram of the study area are shown in Figure 7. There is consistency in the lineament hereby inferred and the previously inferred lineaments in the region [1,11,12].…”
Section: Lineament Study Of the Study Areasupporting
confidence: 86%
See 1 more Smart Citation
“…The lineament density map and the rose diagram of the study area are shown in Figure 7. There is consistency in the lineament hereby inferred and the previously inferred lineaments in the region [1,11,12].…”
Section: Lineament Study Of the Study Areasupporting
confidence: 86%
“…The Earth could be thought of as a large and spherical magnet surrounded by a variable magnetic field. Dipole magnet at the center of the Earth with North and South Pole generates the field [1]. Measured magnetic field at a point is from the superimposition of the magnetic field of geological bodies at the point on the Earth's background magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The upward continued field is determined by taken the product of the upward continued filter in the frequency domain and the Fast Fourier Transform magnetic data. The multiplication result is the inverse Fast Fourier Transform to the space domain in obtaining upward continuation data (Suleiman et al, 2018). However, the residual airborne magnetic data of the study area were upward continued to a height of 500 m, 1000 m, 2000 m and 3000 m (figure 5a-d) so that the short wavelength signals were minimized for enhancement of deeper anomalies effect (i.e.…”
Section: Upward Continuation (Uc)mentioning
confidence: 99%